Nonsense as Autobiography: The Children’s Poems and Family Secrets of Laura E. Richards - Etti Gordon Ginzburg (European Journal of American Studies)
Laura E. Richards’s (1850-1943), the first lady of American nonsense poetry, was among the few nineteenth-century professional women writers who composed literary autobiographies, and the only one who wrote two, one for adult readers and one for children. The present essay argues for reading Laura E. Richards’s nursery and Nonsense rhymes as her third autobiography. Unlike her formal autobiographies, which primarily served to maintain a mythic legacy of her renowned parents, Julia Ward and Samuel Gridley Howe, Richards’s nonsense poetry subtly subverts the constraints of this narrative. Beneath a playful surface, her rhymes reveal insights and tensions that her official autobiographies strategically obscure. By examining Richards’s nonsense verses alongside her autobiographies, personal and historical accounts, and within the broader context of nineteenth-century Nonsense poetry and women’s and children’s literature, this essay argues for a richer, more nuanced understanding of her life and work. In doing so, it repositions Richards and her poetry within the cultural and literary history of her time, offering both the poet and her oeuvre the critical attention they have long been denied.